Protocolo Para El Abordaje Clinico Y/O Quirurgico De Sindrome Abdominal Agudo. Monografía (2025)
This monograph was carried out as a degree work modality, focusing the research on acute abdominal syndrome SAA, the reception of patients with signs of this pathology and taking as a reference authors who describe the clinical, pharmacological and/or surgical management. It is important in equine internal medicine because it is one of the diseases that causes the highest mortality in patients. As a result, the protocols already established in clinical care were compared and an adequate standardization was carried out on the method of resolution of equine colic, the little literature reported on the approach to patients with acute abdominal syndrome was evidenced.